Hepatitis B virus hijacks MRE11-RAD50-NBS1 complex to form its minichromosome. - Kaitao Zhao; Jingjing Wang; Zichen Wang; Mengfei Wang; Chen Li; Zaichao Xu; Qiong Zhan; Fangteng Guo; Xiaoming Cheng; Yuchen Xia (PLoS Pathogens)
Chronic hepatitis B virus (HBV) infection can significantly increase the incidence of cirrhosis and liver cancer, and there is no curative treatment. The persistence of HBV covalently closed circular DNA (cccDNA) is the major obstacle of antiviral treatments. cccDNA is formed through repairing viral partially double-stranded relaxed circular DNA (rcDNA) by varies host factors. However, the detailed mechanisms are not well characterized. To dissect the biogenesis of cccDNA, we took advantage of an in vitro rcDNA repair system to precipitate host factors interacting with rcDNA and identified co-precipitated proteins by mass spectrometry. Results revealed the MRE11-RAD50-NBS1 (MRN) complex as a potential factor. Transiently or stably knockdown of MRE11, RAD50 or NBS1 in hepatocytes before HBV infection significantly decreased viral markers, including cccDNA, while reconstitution reversed the effect. Chromatin immunoprecipitation assay further validated the interaction of MRN complex and HBV DNA. However, MRN knockdown after HBV infection showed no effect on viral replication, which indicated that MRN complex inhibited the formation of cccDNA without affecting its stability or transcriptional activity. Interestingly, Mirin, a MRN complex inhibitor which can inhibit the exonuclease activity of MRE11 and MRN-dependent activation of ATM, but not ATM kinase inhibitor KU55933, could decrease cccDNA level. Likewise, the MRE11 endonuclease activity inhibitor PFM01 treatment decreased cccDNA. MRE11 nuclease assays indicated that rcDNA is a substrate of MRE11. Furthermore, the inhibition of ATR-CHK1 pathway, which is known to be involved in cccDNA formation, impaired the effect of MRN complex on cccDNA. Similarly, inhibition of MRE11 endonuclease activity mitigated the effect of ATR-CHK1 pathway on cccDNA. These findings indicate that MRN complex cooperates with ATR-CHK1 pathway to regulate the formation of HBV cccDNA. In summary, we identified host factors, specifically the MRN complex, regulating cccDNA formation during HBV infection. These findings provide insights into how HBV hijacks host enzymes to establish chronic infection and reveal new therapeutic opportunities.